Lipase activity inhibited by aloenin A: Glycoside from Aloe vera (L.) Burm. f.—In vitro and molecular docking studies. Issue 2 (14th December 2022) - Deora, Neha; Venkatraman, Krishnan
Abstract: Obesity is taking over many parts of the world and has been identified as the second leading cause of preventable death, with a dramatic increase in prevalence over the last two decades. Pancreatic lipase is a lipid‐digesting enzyme that plays an important role in fat metabolism. Inhibiting pancreatic lipase is an attractive target for obesity treatment. Phytochemicals or bioactive compounds/extracts isolated from medicinal plants offer a promising platform for the development of pancreatic lipase inhibitors. This study aims to characterize and investigate the effect of aloenin A, glycoside found in Aloe vera, as a possible inhibitor of pancreatic lipase in vitro and in silico. A. vera extract had an IC50 value of 0.5472 μg/ml, whereas aloenin A had an IC50 value of 14.95 μg/mL and was found to inhibit in a competitive manner. These findings were supported by molecular docking studies, which revealed that aloenin A binds to the substrate binding site with a binding energy of − 7.16 kcal/mol, and this binding site is stabilized by three hydrogen bonds contributed by Phe 77 and Asp 79 . Our findings suggest that the anti‐hyperlipidemic effects of A. vera on pancreatic lipase can be attributed in part to the presence of aloenin A. Abstract : Molecular interaction of Aloenin A with pancreatic lipase.